2007
DOI: 10.1016/j.bbmt.2006.12.449
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Multicenter Trial of Peripheral Blood Stem Cell Sibling Allografts for Acute Myeloid Leukemia in First Complete Remission Using Fludarabine-Cyclophosphamide Reduced Intensity Conditioning

Abstract: The role of allogeneic transplantation in patients with de novo acute myeloid leukemia in first complete remission (AML-CR1) is controversial. Aiming to preserve a graft-versus-leukemia effect, but minimize morbidity and mortality from conditioning-related toxicity and graft-versus-host disease (GVHD), we conducted a prospective multicenter study of reduced-intensity conditioning (RIC) as preparation for peripheral blood stem cell sibling allografts in patients with intermediate or poor risk AML-CR1. Condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…Thirteen (38%) patients relapsed and estimated DFS and OS at 2 years were 56 and 68%, respectively. 42 The current investigation extends these findings, with longer follow-up, to patients of advancing age and recipients of unrelated grafts, 75% of whom were not in first CR at the time of transplantation. Mucositis and SOS were avoided, predominantly donor chimerism occurred in all patients and DLI was not needed to encourage donor engraftment.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Thirteen (38%) patients relapsed and estimated DFS and OS at 2 years were 56 and 68%, respectively. 42 The current investigation extends these findings, with longer follow-up, to patients of advancing age and recipients of unrelated grafts, 75% of whom were not in first CR at the time of transplantation. Mucositis and SOS were avoided, predominantly donor chimerism occurred in all patients and DLI was not needed to encourage donor engraftment.…”
Section: Discussionsupporting
confidence: 59%
“…Grigg et al 42 recently reported results of a clinical investigation using nonmyeloablative CY/Flu to prepare 34 patients with de novo AML in first CR for matchedsibling allotransplantation. Patients experienced relatively low incidences of grades 2-4 aGVHD (21%) and cGVHD (24%).…”
Section: Discussionmentioning
confidence: 99%
“…31 Data from a prospective study with a RIC regimen resulted in a 2-year relapse incidence of 37% following fludarabine and CY conditioning in patients with AML in CR1. 41 With an OS and DFS of 61 and 55% at 2 years, the survival data following treosulfan and fludarabine conditioning in AML patients are in the upper range of those previously reported. Pidala et al, (2011) 38 reported a similar 2-year OS rate of 62% for patients in CR1 following targeted standard dose IV BU/fludarabine conditioning.…”
Section: Discussionmentioning
confidence: 75%
“…43 Similar results for overall and disease free survival compared with the present study were obtained after RIC with fludarabine and CY (68% and 56%, respectively). 41 However, those study patients probably had more favorable disease-specific prognostic profiles and transplant characteristics; 85% of the patients had an intermediate cytogenetic risk, and all patients were in CR1 and received PBSCs from a sibling donor.…”
Section: Discussionmentioning
confidence: 94%
“…73,74 Reduced-intensity allogeneic transplants in AML The ability of reduced-intensity allografts to deliver durable remissions in older patients with high-risk AML has now been demonstrated by a number of groups. 7,9,10,[75][76][77][78][79][80][81] Although longer-term follow-up is still required on these cohorts it is likely that RIC allografts represent a major advance in the treatment of AML in older patients and important questions concerning the optimal reducedintensity regimen and the integration of RIC allografts into the overall management of older patients must now be addressed.…”
Section: The Role Of Allogeneic Transplantation In Management Of Patimentioning
confidence: 99%